2018
DOI: 10.3389/fnmol.2018.00214
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid Signaling at Hypothalamic Steroidogenic Factor-1/Proopiomelanocortin Synapses Is Sex- and Diet-Sensitive

Abstract: We tested the hypotheses that steroidogenic factor (SF)-1 neurons in the hypothalamic ventromedial nucleus (VMN) provide sexually disparate, endocannabinoid (EC)- and diet-sensitive glutamatergic input onto proopiomelanocortin (POMC) neurons. Electrophysiological recordings were performed in hypothalamic slices from intact and castrated guinea pigs, along with in vitro optogenetic experiments in intact male as well as cycling and ovariectomized female NR5A1-Cre mice. In slices from castrated male and female gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 81 publications
(131 reference statements)
1
36
0
Order By: Relevance
“…We have shown previously that long-term exposure to HFD leads to a potentiation of the CB1 receptor-mediated inhibition of glutamatergic transmission at VMN SF-1/ARC POMC synapses in male but not female mice [21]. We then wanted to see if long-term exposure to HFD could also potentiate the NOP receptor-mediated reduction in glutamatergic input at these synapses.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have shown previously that long-term exposure to HFD leads to a potentiation of the CB1 receptor-mediated inhibition of glutamatergic transmission at VMN SF-1/ARC POMC synapses in male but not female mice [21]. We then wanted to see if long-term exposure to HFD could also potentiate the NOP receptor-mediated reduction in glutamatergic input at these synapses.…”
Section: Resultsmentioning
confidence: 99%
“…For the optogenetic studies described in experiments 1–3 that were designed primarily to test the hypothesis that N/OFQ decreases glutamate release at VMN SF-1/ARC POMC synapses in a sex- and diet-dependent manner, recordings were performed in slices from NR5A1-Cre mice that were injected with a ChR2-containing viral vector into the VMN 2–3 weeks prior to experimentation. Once glutamatergic SF-1-expressing fibers (visualized with YFP) impinging on ARC neurons were encountered, functional synaptic connectivity was ascertained by applying a photo-stimulus (25–100-ms pulses delivered every 2 s) from a light-emitting diode (LED) blue light source (470 nm) controlled by a variable 2A driver (ThorLabs, Newton, NJ, USA) that directly delivered the light path through the Olympus 40X water-immersion lens to generate a fast excitatory postsynaptic current (EPSC) as described previously [21]. We then determined whether the neuron under consideration was a likely POMC neuron by prescreening for intrinsic membrane currents like the A-type K + current and the hyperpolarization-activated mixed cation current [37, 39, 40] via the current-voltage (I/V) relationships generated as described in the next paragraph.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Well-executed tissue-specific knockout studies have shown that SF-1 VMH neurons control insulin-mediated protection from diet-induced leptin resistance, weight gain, adiposity, and impaired glucose tolerance (133)(134)(135)(136); and SF-1 neurons are well-known to be critical in mediating diet-induced obesity (72). Tissue-specific knockout studies of SF-1 in the VMH have demonstrated SF-1 as an anorexigenic factor regulated by nutritional status (137), and have shown that SF-1 is required for the development of the complete functional hypothalamic-pituitarygonadal axis, as well as the hypothalamic-pituitary-adrenal axis (64,134,138). These studies are very important clinically because nuclear receptors like SF-1 are some of the Fig.…”
Section: Neuroendocrinolgy Of Obesitymentioning
confidence: 99%